Análise em fluxo e análise in situ como estratégias de melhoramento da seqüência analítica de amostras agronômicas - Lemos, Sherlan Guimarães (Universidade Federal de São Carlos, 2005)
The present work discusses the use of alternative approaches for the improvement of the agronomic sample analytical pathway. It was focused on the elimination of the sampling step, with the in situ soil analysis, or in the measurement step with the adoption of flow analysis procedures, with the development of two analytical systems. The first one was employed in the total nitrogen and its inorganic forms determination in plant and soil samples, based on the Berthelot reaction. The second flow analysis system was developed for phosphorous speciation in seeds and grains samples used in animal nutrition by means a cobalt metallic electrode. For the elimination of the sampling step in the process of soil analysis, an analytical probe prototype was developed (hardware probe, sensors and electronic instrumentation and software algorithms for acquirement, processing, conversion, storage and data transfer) by using PVC membrane ion-selective sensors suitable to be inserted into soils for obtaining in situ and real time information of nutrient assimilation on agricultural soils. Parameters as pH and availability of some nutrients (K+; N, as NO3 - and NH4 +; Ca2+ and P, as H2PO4 -/ HPO4 2-) were evaluated in this stage. Although more systematic studies are needed, the results showed good responses of the studied sensors, and the great applicability of the developed instrumentation in the fertility irrigation monitoring, helping to establish rational processes in agricultural systems.
Flow analysis and in situ analysis as aproaches to the improvement of the agronomic samples analytical pathway
Keywords: Instrumentação; Análise in situ; Análise por injeção de fluxo; Sensor potenciométrico; Agricultura de precisão; Solos; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA